The Incidence of Dysarrhythmias, Their Types and Outcomes in Patients Hospitalized with COVID -19 - Abdulsatar Kamil Faeq (Diyala Journal of Medicine, 2021)
Background: COVID-19 infection started in China and became a pandemic, the SARS-CoV-2 virus mainly affects  the respiratory system but can insult the cardiovascular system as well, higher rate of cardiac arrhythmias noted during the pandemic, and many studies showed that COVID-19 (especially hospitalized patients) can develop different types of arrhythmias which cause higher mortality rate.